Walter Pater : individualism and aesthetic philosophy - Hext, Kate (Edinburgh University Press, 2013)
Explores how Walter Pater and his contemporary aesthetes were influenced by modern philosophies. Repositioning Walter Pater at the philosophical nexus of Aestheticism, this study presents the first discussion of how Pater redefines Romantic Individualism through his engagements with modern philosophical discourses and in the context of emerging modernity in Britain. It also considers the dynamics between form and thought at the fin de siècle, contextualizing its comments in terms of Matthew Arnold, Oscar Wilde and Vernon Lee and others, to offer a fully integrated account of the intellectual cultures and currents in this period. Key Features:. Boldly reassesses Pater's intellectual significance, arguing that he self-consciously poised on the cusp between late-Victorian Romanticism and Modernism Imaginatively combines close readings with cultural and intellectual history and biography to reconsider individualism and philosophical thought in the Aesthetic 'Movement' Provides the most substantial scholarly engagement with Pater's unpublished manuscripts (held at the Houghton Library, Harvard University)
Keywords: Pater, Walter, -- 1839-1894 -- Criticism and interpretation.; Pater, Walter, -- 1839-1894; Literature -- Aesthetics.; Individualism in literature.; Littérature -- Esthétique.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; LITERARY CRITICISM -- General.; Individualism in literature; Literature -- Aesthetics; Criticism, interpretation, etc.